Abstract 054: Transradial Thrombectomy Using "Sheathless PV" Guide Catheter in Armenia: Three‐Year Institutional Experience in 103 Cases - David Sahakyan; Anna Isahakyan; David Marqaryan; Aleksan Petrosyan; Mikayel Grigoryan (Stroke: Vascular and Interventional Neurology)
Introduction Transradial access (TRA) in neuroendovascular procedures has gained popularity in recent years (1). It offers numerous advantages and stimulated development of long flexible large lumen guiding catheters as well as adoption of existing cost‐efficient alternatives used in cardiac and peripheral interventions (2,3). We report our three‐year experience using the Sheathless PV guide catheter (Asahi Intecc, Japan) in a consecutive series of acute stroke patients undergoing endovascular thrombectomy (ET) at a Comprehensive Stroke Center in Yerevan, Armenia. The interest in its use specifically for TRA stemmed from competitive price (∼ $100 per catheter vs ), hydrophilic coating of the outer shaft, as well as lack of femoral closure devices in the country. Methods We retrospectively identified all consecutive acute stroke patients who had undergone ET via TRA from a prospectively maintained institutional stroke database between June 2020 and June 2023. Data were collected on determinants of decision to proceed with TRA‐first approach, baseline patient imaging and clinical characteristics, location of the occlusion, puncture‐to‐reperfusion time (PT‐RT), conversion to transfemoral access (TFA), periprocedural complications, and procedural/clinical outcomes. Results were compared to patients who underwent TFA‐first ET over the same time period. The Mann‐Whitney U‐test was used to analyze the continuous variables and chi‐square test was used for categorical variables. Standardized TRA technique involved exchanging the puncture needle to a short 6Fr introducer first, then over a J‐wire, to a 90cm (0.090" ID/0.110" OD) Sheathless PV guide catheter over a dilator. The dilator was then removed, and a long JR4 diagnostic catheter was used to select cervical vessels over a 0.035 wire and advance the guide over in a triaxial fashion. Results A total of 538 patients underwent ET during the analyzed 3‐year period, of which access was either not recorded, or was other than TRA/TFA in 23 patients (excluded from analysis). Of the remaining 515 patients, 103 had TRA‐first (all using Sheathless PV guide catheter) and 412 had TFA‐first (various guide catheters). The decision to proceed with TRA was at the discretion of the operator and was influenced by presence of bovine arch on CTA (for left anterior occlusions), favorable angle between the right subclavian and the right common carotid arteries (for right anterior occlusions), dominant right vertebral artery or favorable angle of V1 origin (for posterior circulation occlusions). Of 103 TRA cases, 71 (68.9%) were in the right carotid circulation, 18 (17.5%) ‐ in the left carotid circulation, and 14 (13.6%) in posterior circulation. TRA‐>TFA conversion occurred in 5 patients (4.8%), TFA‐>TRA ‐ in 1 patient (0.24%) all of which were due to prohibitive anatomy, rather than guide catheter limitations. There were no significant differences in baseline patient characteristics between the TRA and TFA groups. Angiographic outcomes (TICI 2B or greater) were similar for TRA vs TFA (96.1% vs 93.9%, p=0.39), as were good clinical outcome (discharge mRS 0‐2) rates (58% vs 55.4%, p=0.63). There was a trend towards shorter PT‐RT with TRA (29.5 min vs 38.3 min) although it did not reach statistical significance (p=0.11). No access‐related complications were noted with TRA. Conclusion Transradial thrombectomy using Sheathless PV Guide catheter is safe, effective, and offers substantial cost‐savings and shorter procedural times with low rate of access conversions, similar to other reported TRA thrombectomy series. Randomized trials are needed to validate its rates of technical success and complications against other frequently‐used TRA guide catheters.